Pengaruh Rebusan Daun Sirsak (Annona Muricata Linn) Terhadap Penurunan Kadar Asam Urat di Puskesmas Indrapuri Aceh Besar - Urip Pratama; Nora Wardati; Mansuriza Mansuriza (Lembaga Pengembangan Kinerja Dosen, 2024)
The prevalence of arthritis gout in the world is 34, 2% dominated by degenerative diseases found in the elderly. The increase in gout incidences not only occurs in developed countries but also developing countries such as Indonesia. This study aimed to examine the effects of soursop leaf decoction on reducing uric acid levels in Indrapuri Public Health Center, Aceh Besar. This study used a quasi-experimental design with a pretest-posttest approach. The population was 203 gout sufferers, while the sample was 22 patients, chosen using the Random Sampling technique. This study was carried out on May 2nd – 18th, 2024 with the univariate and bivariate questionnaire analysis using a Paired T-test. The results prove that before the soursop leaf decoction treatment, the average uric acid level of the respondents were 7, 08 mg/dl. However, after the treatment, the uric acid level was 5, 97 mg/dl. It indicates that the uric acid level decreased to 1,109 mg/dl with a ρ-value 0,000. This result proves that soursop leaf decoction treatment (Annona Muricata Linn) is effective in reducing uric acid level. It hopes that the community will be aware of health on the non-pharmacological treatment of uric acid by utilizing soursop leaf decoction